ANALISIS EKONOMI USAHATANI PADI SAWAH DI KECAMATAN RAMBAH SAMO, KABUPATEN ROKAN HULU - Darus Darus; Saipul Bahri; Ujang Paman Ismail (UIR Press, 2015)
Development of rice farming in Rambah Samo District Rokan Hulu Regency is facing various problems. It can be known from the relative low development of cultivated area, production rate, and income received by farmers. The purpose of this study was to analyze the provision of farm inputs, cost of production, yields, revenue, profit, and efficiency of rice farming in District Rambah Samo. The research used survey, conducting in Rambah Samo District Rokan Hulu Regency from September to December 2014. A total of 65 samples were selected by using simple random sampling method. The results showed that the inputs for rice farming were available as required by farmers. The production averaged as much as 3,208.86 kg/ha and required costs an average of Rp 5.611.217,66. Yield derived from rice faming was Rp 11,808,610.46 and profit was Rp 6,197,392.81 on average with family income reached as Rp 9,074,352.77. Rice farming in survey area was economically efficient with RCR value of 2.09.